General linguistic characteristics of linguistic units of variability (Eurasian Journal of Philology Science and Education, 2018)
In the article a comparative analysis of the problems of variability in the Kazakh and Russian languages is carried out. Based on the opinion of the Kazakh linguistists and Russian scientists, the authorconsiders the general linguistic characteristic of variability of language units. The concept of varianthasn’t been exactly defined for the types of variation, different levels and aspects of language. Therefore,on the basis of the analysis of opinions of scientists concerning this problem variability covers intralinguistic and extralinguistic factors, existence of the literary language together with different languagevariants, and also national and regional types of language.